Taphonomic analysis of surface lithic assemblages in aeolian contexts of the north coast of San Matías gulf, Río Negro (Argentina) - Carranza, Eugenia (Instituto de Arqueología, Facultad de Filosofía y Letras, Universidad de Buenos Aires, 2023)
The northern sector of the San Matias Gulf has archaeological loci and radiocarbon dates of human occupations corresponding to the Middle and Late Holocene. Previous results suggest that the interaction between aeolian processes (corrosion, transport, and deposition) and the characteristics of the assemblage (artifact granulometric composition) influence the archaeological record configurations. In this paper, the results from the taphonomic analyses of surface lithic assemblages recovered from four archaeological sites are presented and compared. The localities are located mainly on two types of geoforms (dunes and old marine terraces) with differential preservation. Besides, the results of the technomorphological analyses that are relevant for assessing the postdepositional history of the artifacts and the potential taphonomic biases are presented and integrated. The results obtained allowed us to identify general trends. The taphonomic evidence suggests conditions of greater relative stability in the assemblages recovered in dunes and less stability for assemblages from terraces. For the technological aspect, previous studies are resumed, emphasizing specific attributes and their frequency in the different samples. An integrative analysis of these two analytical dimensions allowed us to reconstruct the various postdepositional trajectories of the assemblages linked to the different locations, estimate their differential representation, and contextualize the human occupations in the different coastal spaces over time.